Implementação em software da codificação de canal em ADSL: um estudo de caso sobre os efeitos do ruído impulsivo na transmissão de vídeo - CORRÊA, Fernanda Regina Smith Neves (Universidade Federal do Pará, 2012)
This work describes the implementation in software of the channel coding used in the ADSL standard. The theory of channel coding is described, as well as the channel coding implemented in the Software Modem ADSL using the development environment Ptolemy II. The implementation of a impulsive noise model is also presented. To ensure that the implementation meets the ADSL standard, tests using the DSL systems analyzer TraceSpan are described. This work also presents an application example of the Software Modem ADSL, characterized by a study case on the e ects of impulsive noise in the video transmission, analyzing the impact of some parameters of channel coding in the correction of errors.